Stability of aqueous film with a photo-responsive surfactant - Nguyen, C.; Yusa, S.; Phan, Chi (Journal of Chemical Engineering of Japan, 2016)
© 2016 The Society of Chemical Engineers, Japan.A cationic azobenzene-containing surfactant, which can be converted reversibly from a cis to a trans conformation, was synthesized. A single liquid thin film containing this surfactant was studied under different light conditions to provide new insights into the foaming behavior of the surfactant. The stability of the thin film was quantified in terms of lifetime and tensile strength. It was found that the lifetime of the thin liquid film was dramatically increased, from a few minutes to a few hours, by UV irradiation regardless of the initial trans/cis fraction. In contrast, the film tension changed insignificantly for all conditions. The obtained results indicated that foaming control by photo-responsive surfactant is driven by the molecular arrangement with the thin aqueous film, rather than the tensile strength. The results provide an important basis for industrial application of the photo-responsive surfactants.